1998
DOI: 10.1039/a803655a
|View full text |Cite
|
Sign up to set email alerts
|

The effect of substitution of the C–F group for the C–H group in crystal packing as well as thermal behaviour

Abstract: Fig. 3 Perspective view of F3•MeOH. For clarity, fluorine and oxygen atoms are represented by discriminated ellipsoids, and hydrogen atoms are omitted. Hydrogen bonds are specified by dotted lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 7 publications
1
21
0
Order By: Relevance
“…The F Á Á Á p (Ar F ) atom-to-face interaction featured perpendicular orientation of the C-F bond with respect to aromatic ring was observed for some compounds bearing fluorinated aromatic groups [22,23,29]. In particular, such an interaction was identified for (C 6 F 5 -CH N-) 2 derivative in front of the overall herringbone packing motif featured the F Á Á Á p separation of 3.07 Å [23].…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The F Á Á Á p (Ar F ) atom-to-face interaction featured perpendicular orientation of the C-F bond with respect to aromatic ring was observed for some compounds bearing fluorinated aromatic groups [22,23,29]. In particular, such an interaction was identified for (C 6 F 5 -CH N-) 2 derivative in front of the overall herringbone packing motif featured the F Á Á Á p separation of 3.07 Å [23].…”
Section: Resultsmentioning
confidence: 93%
“…Table 2). and 2.54 Å , respectively [24] (C Ar Á Á Á C Ar contact, 3.54 Å [22]). Altogether, p-stacking interactions and H-bonds afford 2D supramolecular architecture of the 1 crystal (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 In other respects, the basic compound triphenylmethanol has been shown to selectively enclathrate methanol and DMSO in its crystal lattice 4 while more bulkily substituted triphenylmethanol derivatives and analogous triarylmethanols demonstrate corresponding inclusion formation with other guest solvents. 8,9 In all these latter structures, O-H⋯π 10 and halogen⋯π 11,12 interactions have proven to dominate the crystal lattices while conventional O-H⋯O hydrogen bonding 13 is prevented from steric reason. 8,9 In all these latter structures, O-H⋯π 10 and halogen⋯π 11,12 interactions have proven to dominate the crystal lattices while conventional O-H⋯O hydrogen bonding 13 is prevented from steric reason.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of¯uorine in molecular crystals and its in¯uence on crystal packing have been comparatively rarely studied [for examples, see Hayashi & Mori (1998) and Renak et al (1999)], given the wealth of information available on the effect of the F atom in biological chemistry (Filler et al, 1993). The interactions of organic¯uorine with other atoms within a crystal lattice are weak and, indeed, it has been observed that, when organically bonded,¯uorine hardly ever acts as a hydrogen-bond acceptor (Dunitz & Taylor, 1997).…”
Section: Commentmentioning
confidence: 99%